2016
DOI: 10.15252/embj.201593489
|View full text |Cite
|
Sign up to set email alerts
|

DnaJ/Hsc70 chaperone complexes control the extracellular release of neurodegenerative‐associated proteins

Abstract: It is now known that proteins associated with neurodegenerative disease can spread throughout the brain in a prionlike manner. However, the mechanisms regulating the trans-synaptic spread propagation, including the neuronal release of these proteins, remain unknown. The interaction of neurodegenerative diseaseassociated proteins with the molecular chaperone Hsc70 is well known, and we hypothesized that much like disaggregation, refolding, degradation, and even normal function, Hsc70 may dictate the extracellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
153
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(171 citation statements)
references
References 101 publications
9
153
1
Order By: Relevance
“…Although there is evidence that supports the neuronal release of tau [1, 9, 10, 56], our data also demonstrate that soluble intracellular phospho-tau could be toxic for microglia after phagocytosis. The phagocytic capacity of microglial cells is highly induced by apoptotic signals in the affected neurons [34, 52].…”
Section: Discussioncontrasting
confidence: 54%
“…Although there is evidence that supports the neuronal release of tau [1, 9, 10, 56], our data also demonstrate that soluble intracellular phospho-tau could be toxic for microglia after phagocytosis. The phagocytic capacity of microglial cells is highly induced by apoptotic signals in the affected neurons [34, 52].…”
Section: Discussioncontrasting
confidence: 54%
“…Although the transcellular spread of tau pathology has become a well-known, experimentally-confirmed phenomenon, the mechanisms through which this process occur have however remained elusive. It was recently reported that the internalisation of tau K18 fibrils occurs via binding with heparan sulphate proteoglycans [46] whilst the extracellular release of 4R0N tau occurs by exocytosis mediated by interaction with the DnaJC/Hsc70 molecular chaperone complex [47]. It however remains unknown as to whether all tau isoforms and fragments and their frontotemporal dementia variants are internalised and secreted through these same processes.…”
Section: Discussionmentioning
confidence: 99%
“…Its overexpression leads to an increase in the concentration of tau in cell culture models, while an Hsc70 inhibitor causes a decrease in tau concentration in cell cultures and rescues long-term potentiation deficits in tauopathy model mouse brain slices (22,36). Hsc70 may also play roles in enhancing tau's association with microtubules (23) and in modulating the extracellular release of tau (37). While it is unclear how Hsc70 affects tau fibril formation, it has been shown to block the formation of fibrils by another amyloid-prone protein, α-synuclein, and even disaggregate pre-formed α-synuclein fibrils when combined with co-chaperones from the Hsp40 and Hsp110 families (33,38).…”
mentioning
confidence: 99%